Analysis of Public Management in Network Governance for Transit-Oriented Development in Jakarta (Study: Integrated Transportation of Blok M - Sisingamangaraja) - Vishnu Juwono; Ferdy Riansyah Putra; Shanen Patricia Angelica; Ilham Pambudi (Jurnal Borneo Administrator, 2025)
The Provincial Government of DKI Jakarta is transitioning from Car-Oriented Development (COD) to Transit-Oriented Development (TOD), requiring effective public management in network governance to ensure transportation integration. However, challenges such as spatial flexibility, building regulations, incentives, and institutional coordination persist. This study analyzes public management within network governance in TOD areas, focusing on the Blok M-Sisingamangaraja corridor using Mu & de Jong’s (2016) framework. Employing a post-positivist qualitative approach, data collection includes in-depth interviews with ten informants and literature reviews. Findings indicate that network governanceimplementation in TOD management is not entirely optimal, with three key gaps: (1) Awareness of the plurality of perceptions, interests, and objectives, (2) Metagovernance, process management, and network structuring, and (3) Searching for common ground. These challenges hinder effective collaboration between stakeholders, including the government, private sector, and local communities. The study concludes that enhanced public management strategies are needed to strengthen TOD governance in Jakarta, with recommendations including increasing stakeholder awareness, improving public participation, and establishing clear regulatory frameworks to enhance institutional coordination